Bioprospecting South African indigenous fruits byproducts as natural antioxidants in processed meat products - Pfukwa, Trust Mukudzei (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhDFoodSc)--Stellenbosch University, 2022.